Genetic and Cellular Interaction During Cardiovascular Development Implicated in Congenital Heart Diseases - Kodo, Kazuki; Uchida, Keiko; Yamagishi, Hiroyuki (Frontiers in Cardiovascular Medicine, 2021)
Congenital heart disease (CHD) is the most common life-threatening congenital anomaly. CHD occurs due to defects in cardiovascular development, and the majority of CHDs are caused by a multifactorial inheritance mechanism, which refers to the interaction between genetic and environmental factors. During embryogenesis, the cardiovascular system is derived from at least four distinct cell lineages: the first heart field, second heart field, cardiac neural crest, and proepicardial organ. Understanding the genes involved in each lineage is essential to uncover the genomic architecture of CHD. Therefore, we provide an overview of recent research progress using animal models and mutation analyses to better understand the molecular mechanisms and pathways linking cardiovascular development and CHD. For example, we highlight our recent work on genes encoding three isoforms of inositol 1,4,5-trisphosphate receptors (IP3R1, 2, and 3) that regulate various vital and developmental processes, which have genetic redundancy during cardiovascular development. Specifically, IP3R1 and 2 have redundant roles in the atrioventricular cushion derived from the first heart field lineage, whereas IP3R1 and 3 exhibit redundancy in the right ventricle and the outflow tract derived from the second heart field lineage, respectively. Moreover, 22q11.2 deletion syndrome (22q11DS) is highly associated with CHD involving the outflow tract, characterized by defects of the cardiac neural crest lineage. However, our studies have shown that TBX1, a major genetic determinant of 22q11DS, was not expressed in the cardiac neural crest but rather in the second heart field, suggesting the importance of the cellular interaction between the cardiac neural crest and the second heart field. Comprehensive genetic analysis using the Japanese genome bank of CHD and mouse models revealed that a molecular regulatory network involving GATA6, FOXC1/2, TBX1, SEMA3C, and FGF8 was essential for reciprocal signaling between the cardiac neural crest and the second heart field during cardiovascular development. Elucidation of the genomic architecture of CHD using induced pluripotent stem cells and next-generation sequencing technology, in addition to genetically modified animal models and human mutation analyses, would facilitate the development of regenerative medicine and/or preventive medicine for CHD in the near future.